The influence of internal audit, motivation, and work environment on employee performance - Bahtiar, Arief; Putra, Ridho Gemilang; Meidawati, Neni; Puspaningsih, Abriyani (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
This study aims to determine the effect of internal audit, motivation, and work environment on employee performance at PT Sreeya Sewu Indonesia. The research population is all employees of PT Sreeya Sewu Indonesia who work for the company, located in Bogor, West Java, with a sample of 39 respondents. Methods of data analysis and hypothesis testing use multiple regression methods. The study results prove that internal audit, motivation, and work environment positively and significantly affect employee performance. The result of the study shows company must continue to improve planning and supervision in each audit implementation. The company also must pay attention to salary increases, pension plan, provide opportunities for promotions, and give appreciation toward employee performance. Another thing that must be considered by the company is to pay attention to the improvement of employees’ knowledge.